Pemberdayaan Wirausahawan Muda Melalui Pelatihan Penyusunan Studi Kelayakan Usaha, Proposal Usaha dan Analisis Laporan Keuangan di Kabupaten Pemalang, Jawa Tengah - Indah Purwanti; Wahid Wahyu Adi Winarto; Nia Sucianti (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
Our young generation, in this case, are important factor in determining the progress of MSME (Micro, Small and Medium Enterprises) because many of them have great potential to develop. Their role in developing the MSME business depends on their ability to develop good business management and financial management. This empowerment program that we carry out invites young people to become entrepreneurs who can develop their business through training in preparing business feasibility proposals and processing financial reports. In this training program, we use the lecture, tutorial, and discussion methods which are carried out in different stages. The benefits of the training program for entrepreneurs include; being able to believe in the feasibility of their business plan, before starting implementation, having guidelines for running their business, such as the allocation of own funds or loans and schedules for repayment; components of costs and revenues that will be obtained, and can anticipate things that might be detrimental or disrupt the running of the company so that they will be able to prepare alternative solutions.